A response to the critique of gender issues in computer-supported learning - Cathy Gunn; Sheila French; Hamish McLeod; Mae McSporran; Gráinne Conole (Association for Learning Technology, 2002)
We find the critique of our paper both interesting and informative. The author raises a number of points as a caution against oversimplification of the issues surrounding gender and computer-supported learning. We fully acknowledge the difficulty of reporting findings from a number of studies and of attempting to define or analyse the complex interaction of already complex concepts such as gender, identity and behaviour within computer-supported learning environments.